Circulating cell‐free BRAFV600E as a biomarker in children with Langerhans cell histiocytosis. (25th April 2017) - Héritier, Sébastien; Hélias‐Rodzewicz, Zofia; Lapillonne, Hélène; Terrones, Nathalie; Garrigou, Sonia; Normand, Corinne; Barkaoui, Mohamed‐Aziz; Miron, Jean; Plat, Geneviève; Aladjidi, Nathalie; Pagnier, Anne; Deville, Anne; et al.
Summary: The BRAF V600E mutation is reported in half of patients with Langerhans cell histiocytosis (LCH). This study investigated the detection of the BRAF V600E allele in circulating cell‐free (ccf) DNA in a paediatric LCH cohort. Children with BRAF V600E ‐mutated LCH were investigated to detect ccf BRAF V600E at diagnosis ( n  = 48) and during follow‐up ( n  = 17) using a picolitre‐droplet digital PCR assay. At diagnosis, ccf BRAF V600E was positive in 15/15 (100%) patients with risk‐organ positive multisystem (RO+ MS) LCH, 5/12 (42%) of patients with RO− MS LCH and 3/21 (14%) patients with single‐system (SS) LCH ( P  <   0·001, Fisher's exact test). The positive BRAF V600E load was higher for RO+ patients (mean, 2·90%; range, 0·04–11·4%) than for RO− patients (mean, 0·16%; range, 0·01–0·39) ( P  =   0·003, Mann–Whitney U test). After first‐line vinblastine‐steroid induction therapy, 7/7 (100%) of the non‐responders remained positive for ccf BRAF V600E compared to 2/4 (50%) of the partial‐responders and 0/4 of the complete responders ( P  =   0·002, Fisher's exact test). Six children treated with vemurafenib showed a clinical response that was associated with a decrease in the ccf BRAF V600E load at day 15. Thus, ccf BRAF V600E is a promising biomarker for monitoring the response to therapy for children with RO+ MS LCH or RO− LCH resistant to first‐line chemotherapy.